# Simplify the expression (3x-1) ²-9x² + 4 and find its value at x = -1

July 29, 2021 | education

| To simplify the expression (3x – 1) ^ 2 – 9x ^ 2 + 4, open the parentheses and give similar terms.

To open the parentheses, we need the formula for abbreviated multiplication by the square of the difference:

(a – b) ^ 2 = a ^ 2 – 2ab + b ^ 2.

Let’s apply it:

(3x – 1) ^ 2 – 9x ^ 2 + 4 = 9x ^ 2 – 6x + 1 – 9x ^ 2 + 4 = 9x ^ 2 – 9x ^ 2 – 6x + 1 + 4 = – 6x + 5.

We find the value of the expression at x = – 1, for this we substitute in the simplified expression x = – 1, we get:

– 6 * (- 1) + 5 = 6 + 5 = 11.

Answer: – 6x + 5; for x = -1, the expression gets a value equal to 11.

One of the components of a person's success in our time is receiving modern high-quality education, mastering the knowledge, skills and abilities necessary for life in society. A person today needs to study almost all his life, mastering everything new and new, acquiring the necessary professional qualities.